Effect of Feeding Fermented Leucaena leucocephala Seed Meal on Growth and Protein Content of Osphronemus gouramy Juvenile - Putri Dista Ananda; Safrida Safrida; Khairil Khairil; Hasanuddin Hasanuddin; Asiah M.D. (Department of Aquaculture, 2022)
Gouramy (Osphronemus gouramy Lac.) is one of the original fish from Indonesia that lives in fresh water and has high economic value because of its dense texture, high nutrition, and delicious taste so that it is widely favored by Indonesians. The results of juvenile cultivation activities have not been going well so far, this is because the growth of gouramy’s juvenile is slower than the growth of other freshwater fish’s juvenile. One alternative that can increase the growth and protein content of gouramy juvenile is to utilize of the availability of lamtoro seeds. The purpose of this study was to determine the effect of feeding lamtoro seed fermentation on growth and protein content of gouramy’s juvenile. This study used experimental method with a completely randomized design (CRD with 6 treatments and 4 replications). Data were analyzed using Analysis of Variance Test (ANOVA) and further test in the form of Honest Significant Difference (Tukey HSD Test) at the 95% confidence level. The results showed that P3 with the addition of fermented lamtoro seed flour 40% can increase the growth and protein content of gouramy juvenile. The conclusion of this study was lamtoro seed fermented feed has effect in increasing growth and protein content of gouramy’s juvenile.